Problems Faced by the Teachers in Teaching Mainstream Curriculum to Visually Impaired Students in Pakistan - Fauzia Malik; Mahmood, Uzma (JIE, 2025)
The study was designed to find out overall problems faced by the teachers in teaching curriculum to visually impaired students. The objectives of the study were to identify problems faced by the teachers (public and private) in curriculum for visually impaired students, to recommend strategies to minimize problems faced by teachers in curriculum. The study employs a mixed-method research design, combining qualitative interviews with teachers and quantitative questionnaire data to provide a comprehensive analysis. The study has established that Schools do not have appropriate teaching and learning resources to help students with the visual impairment and be able to assimilate better in classroom. The study further found that there is a lack of cooperation, or contribution by the parents in the educational matters of their children. Another hindrance is that teachers were not trained to teach students with visual impairment. Apparatus and teaching aids are either inadequate or outdated and not suitable for imparting satisfactory level of education. Students are therefore not assessed based on their individual capability and skill level. The skill and knowledge of teaching the visually impaired is on the decline alarmingly. This trend needs to be halted. It is as statistically proven that a modified curriculum for the visually impaired is a dire need of the time.